Perbandingan Sistem Permodalan Konvensional dan Syariah Terhadap Pedagang Pasar Sentral Watampone dalam Pengembangan Usaha - Jusmayati Jusmayati; St Habibah St Habibah (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to find out how the comparison of conventional and sharia capital systems inbusiness development. The author also examines the advantages and disadvantages ofconventional and sharia capital. They are entitled to get a capital loan in accordance with theterms and agreements between the bank and the customer for the next stage. Traders have theright to what they want, whether they will be so-so or will develop their business with loan capitalprovided by the bank. The results of this study indicate that the capital system provided by bankfinancial institutions can help develop the merchant business, between conventional banks andIslamic banks have similarities and differences in providing loan capital to traders where banksuse interest from these loans while Islamic banks use profit sharing not many sword ownerschoose a capital system with banks that use interest systems because conventional banks donot complicate customers differently than more complicated Islamic banks. So that peoplechoose conventional banks that are already evident in the al-qur'an that interest equals usury.